Financing fiscal deficits. Intertemporal approach under different exchange rate regimes - Descalzi, Ricardo L. (2017)
Fil: Descalzi, Ricardo L. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.